0076 The "dress Rehearsal" Method - A New Paradigm For Introducing Simulation Based Team Training?. (1st November 2014) - Martin, Fiona; Hellewell, Alistair; Martin, Alastair; Cockcroft, James
Abstract : Background: Simulated scenarios are a good way of training teams of healthcare workers in the management of rare events. Staff unfamiliar with simulation are worried about taking part in a scenario. In drama and music, rehearsals form a large part of preparation for performance. We established a theatre team training programme using a "dress rehearsal" method to practise pre-defined critical incidents avoiding intimidation of team members. We have experienced a rapid culture change in favour of simulation. The "dress rehearsal" method has allowed rapid progression to higher levels of team training. Outline: We initiated a programme of critical incident simulation for operating theatres in our trust. Participants, especially nursing staff and ODPs, were reluctant to engage and felt it was a test. To overcome this, we delivered the sessions as a "dress rehearsal". We run a session as a normal theatre list. The staff know the critical incidents to take place. Foreknowledge of the critical events reduces staff anxiety without detracting from the learning experience of the scenario. Participants have "learned their lines" which means that the scenarios are managed with forethought. Delivering the sessions in situ maximises realism and enables environmental testing which yields system errors. Specialty specific cases allow the scenarios to deliver in-depth specialty learning Results: All staff who gave feedback were very positive Change in culture. Word has been spread that the session is worthwhile and not intimidating. Previous participants are keen to get involved in other simulation work. Staff who have yet to participate are now lobbying us for their theatre to be next. Conclusion: The "dress rehearsal" method of introducing simulation to multi-professional teams has led to a culture change which has promoted the use of simulation within the theatre environment. We believe it is a good way of introducing team training without jeopardy.